THE UNDERSTANDING OF MEANING IN LITERARY LEARNING THROUGH SCIENTIFIC APPROACH - Juliaans E R Marantika (JURNAL TAHURI, 2020)
The works of literature greatly contribute to a nation's characteristics and personality. Understanding a literary work means being able to grasp moral values ​​or messages that are useful for social life. However, understanding a literary text is not as easy as understanding a non-literary text. The main reason is that the literary text bound to several forming conventions such as the language convention, literature, and cultural conventions. To understand this, students must be trained through education and teaching. Literary learning which can produce a good understanding should prioritize the process to familiarize students with the conventions that bind literary works through heuristic and hermeneutic reading. The 2013 curriculum, requires a change in the paradigm of the teacher's thinking towards planning and implementing learning based on a scientific approach. The important point that should be understood by the teachers is literary learning, according to any curriculum, aims to provide literary knowledge understanding and appreciation to the students. It indicates that literary learning should be designed not only to improve literary knowledge but also to express the values that ​​contained. The application of semiotic analysis methods in literary learning including short stories or poetry can be adapted to the steps of teaching based on the scientific approach known as 5 principles, which are observing, questioning, exploring, associating, and communicating/presenting as required by 2013 curriculum. In this context, the expression of the meaning of literary texts is done through observing, reading, repeating, comparing texts (heuristic readings), and continued by exploring and tracing the meaning of texts (hermeneutic readings) and drawing conclusions as a whole